1990
DOI: 10.3109/08923979009006474
|View full text |Cite
|
Sign up to set email alerts
|

Protein a Induced Abrogation of Cyclophosphamide Toxicity is Associated with Concomitant Potentiation of Immune Function of Host

Abstract: This report confirms our previous observation that protein A (PA) of Staphylococcus aureus Cowan I reduces the cyclophosphamide (Cy) induced toxicity. PA treated animals recover quickly from the toxic effects of Cy. We have exhaustively studied the role of specific and nonspecific immunity in the protection of the animals. It was observed that PA helped the animals in the accelerated regeneration of leukocytes of blood (p less than 0.001) and different lymphoid organs like thymus (p less than 0.001), spleen (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Toxic effects of CP towards humoral immunity, especially B-cell functions are well documented and we have also reported the same in our previous investigations. 13,17,31,32 E. officinalis at a dose of 100 mg/kg caused an increase in the splenic cell counts. Conversely, it decreased the relative organ weight of spleen.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Toxic effects of CP towards humoral immunity, especially B-cell functions are well documented and we have also reported the same in our previous investigations. 13,17,31,32 E. officinalis at a dose of 100 mg/kg caused an increase in the splenic cell counts. Conversely, it decreased the relative organ weight of spleen.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have been conducted using CP along with some protective agent(s). For example, Ray et al, 11 Dohadwala and Ray 12 and Zaidi et al 13 have shown that the immunomodulating agent, protein A of Staphylococcus aureus, protects animals from CPinduced toxicity. We have also shown that CPinduced in vitro and in vivo mutagenicity could be inhibited by the herbs Cassia occidentalis and Emblica officinalis.…”
Section: Introductionmentioning
confidence: 99%
“…SPA treatment was associated with increases in glutathione‐S‐transferase. One prior safety study of intravenous SPA in the monkey was found in the published literature . However, this non‐GLP pilot study did not characterize the origin or purity of the SPA utilized for dosing and contained no toxicokinetic information on the plasma exposures attained.…”
Section: Discussionmentioning
confidence: 99%
“…CP also induces mutagenicity in mice (Sharma et al, 2001). The suppressive effects of CP on lymphoid organs, WBC counts and other immune functions are well documented (Zaidi et al, 1990;Bin-Hafeez et al, 2001;Jena et al, 2003;Ramadan et al, 2011;Shreder et al, 2012).…”
Section: Introductionmentioning
confidence: 96%